Quantification of surface roughness effect on elastically backscattered electrons. (15th May 2014) - Ding, X.; Da, B.; Gong, J. B.; Mao, S. F.; Li, H. M.; Ding, Z. J.
<x xml:space="preserve">Abstract</x> Electron inelastic mean free path can be obtained from a measured elastic peak electron spectroscopy spectrum combined with a Monte Carlo simulation. It is thus necessary to know the influence of various experimental factors to the measured and calculated results. This work investigates the effect of the surface roughness or the surface topography on the intensity of the elastic peak. A Monte Carlo simulation, by taking into account of realistic surface roughness for both Gaussian and non‐Gaussian type rough surfaces experimentally prepared, has been employed to study the surface topography effect. The simulations of elastic peak electron spectroscopy were performed for both planar and rough Al and Cu surfaces and for varied primary energies ranging from 200 to 2000 eV. To quantify the surface roughness effect, the surface roughness parameter is introduced according to the ratio of elastic peak intensities between a rough surface and an ideal planar surface. Simulation results have shown that surface roughness parameter is important in a certain range of emission angle and particularly for large emission angles. For grazing emission, the elastic peak intensity can be largely enhanced by roughness even at nanometer scale. Copyright © 2014 John Wiley & Sons, Ltd.